The Benefits from Climate Information as a Source of Empowerment: Findings from an Experiment in Zambia - Kramer, Berber; Trachtman, Carly; Zuze, Linda (2023)
In this note, we summarize our experimental work in Zambia that seeks to evaluate the benefits of Climate Information Services (CIS) for smallholder farming households. To quantify the benefits of CIS, we compare participants’ simulated agricultural investment decisions both with and without the provision of forecasts and advice. Additionally, we invite couples to play the game both as individuals and jointly to test whether CIS information can help align individuals’ preferred investment choices with jointly made investment decisions.